Post-marathon wearing of Masai Barefoot Technology shoes facilitates recovery from race-induced fatigue: an evaluation utilizing a visual analog scale - Nakagawa K; Obu T; Kanosue K (Dove Medical Press, 2014)
Kento Nakagawa, Takashi Obu, Kazuyuki KanosueFaculty of Sport Sciences, Waseda University, Tokorozawa, Saitama, Japan Purpose: To investigate the potential benefit of post-race wearing of unstable shoes (Masai Barefoot Technology [MBT]) on recovery from marathon race–induced fatigue.Patients and methods: Forty-five runners who participated in a full marathon race were divided into three groups: 1) MBT shoes, 2) trail running shoes, and 3) control (CON). Participants ran a full marathon with their own running shoes, and then put on the assigned shoes immediately after the race. They continued to wear the assigned shoes for the ensuing 3 days. The CON group wore their usual shoes. Estimates of post-race fatigue were made by the participants on questionnaires that utilized a visual analog scale. Estimates were made just after the race, as well as for the next 3 days.Results: The subjective fatigue of the MBT group was lower than that of the CON (P<0.05) or trail running shoe groups (P<0.05) on day 3.Conclusion: MBT shoe intervention can promote recovery from the fatigue induced by running a full marathon.Keywords: footwear, VAS, full marathon